Metode akselerasi hafalan al Qur’an di Pesantren al-Qur’an Nuur Ahmad Lombok - Ahyar Rosidi (Prodi Tadris Matematika-UIN Mataram, 2021)
This service research aims to determine the application of the method of memorizing the Qur'an at the Al-Qur'an Islamic Boarding School Nuur Ahmad Lombok. Memorizing the Qur'an is a worship that began during the time of the Prophet Muhammad and has grown to the present day. Over time, many methods were born to make it easier to memorize the Qur'an. This activity is the final report of the KKP-DR UIN Mataram which aims to find out the method used in memorizing the Qur'an at the Al-Qur'an Islamic Boarding School Nuur Ahmad Lombok. The method in accelerating memorization used is the FOURT4 method (Tahsin, Tahfidz, Tarjamah, Tafsir). This method has proven useful in facilitating students in memorizing the Qur'an, gaining an understanding of the Qur'an, strengthening and maintaining memorization, fostering motivation in memorizing the Qur'an and creating an intensive relationship between students and the Qur'an. an. The results of this service activity are expected to be a reference for existing Tahfidz institutions.